ANALISIS MOTIVASI DAN DISIPLIN KERJA SERTA PENGARUHNYA TERHADAP PRESTASI KERJA KARYAWAN PADA CV. GRAHA INDAH SARI PALEMBANG - A Akila (JURNAL KOMPETITIF, 2016)
The purpose of this study was to determine the effect of motivation and discipline on employee performance in CV. Graha Indah Sari Palembang. The population in this study as many as 52 people. The sampling technique using saturated sampling technique, all populations sampled in the study. The data collection technique using a questionnaire. This research method using descriptive method with quantitative approach using a questionnaire as a data collection tool and use the technique multiple linear regression analysis to measure the impact of independent variables on the dependent variable is the motivation and discipline as an independent variable (X) and work performance of employees as the dependent variable (Y).The results showed : 1) Motivation and discipline have a positive and significant impact on employee performance in CV. Graha Indah Sari Palembang, 2) motivation has a positive and significant impact on employee performance in CV. Graha Indah Sari Palembang, and 3) Discipline of work has positive and significant impact on employee performance in CV. Graha Indah Sari Palembang. Keywords: motivation, work discipline and work performance